Analysis of journal content characteristics and metrics reported in the Clarivate Analytics Journal Citation Reports and Web of Science Core Collection Agricultural Engineering categories - Wang, Yuanjie; Gassman, Philip W.; Wang, Yingkuan; Pu, Yingjun (International Journal of Agricultural and Biological Engineering, 2018)
The Clarivate Analytics Journal Citation Reports (JCR) and Web of Science (WoS) platforms are arguably the most influential journal citation/metric databases worldwide. Journals must first be indexed in the WoS Core Collection (CC) before being indexed in the JCR. The JCR and WoS platform are separate Clarivate Analytics products, but the JCR is included in the WoS platform for organizations that purchase both databases. The analysis for this study focused on citation data reported in the 2017 JCR (based on 2016 citation data) and other data reported in the WoS CC up to 2016. A total of 14 journals are indexed in the 2017 JCR agricultural engineering category; however, only 13 journals are analyzed in this because one journal was listed by mistake. Six of the 13 journals are published by large for-profit publishers (i.e., Elsevier B.V. or Springer Verlag) and the other seven are published by respective professional societies. The journals were analyzed as a function of type (specialty versus comprehensive), type of publisher and publication frequency, metrics such as the Journal Impact Factor (JIF), volumes of articles published by year and journal, and the source institutions and countries of published articles. Bioenergy- and industrial crop-focused journals included in the 2017 JCR agricultural engineering category manifest the strongest overall metrics, as evidenced by relatively high JIF scores: Bioresource Technology (4.917), Biomass and Bioenergy (3.219) and Industrial Crops and Products (3.181). In contrast, the highest JIF reported in the 2017 JCR for a comprehensive agricultural engineering journal was 2.044 for Biosystems Engineering. During 2006 to 2016, the number of articles indexed in the Core Collection for the JCR agricultural engineering category rose from 1,124 to 4,078, an increase of 263%. Over 70% of the total articles published in 2016 were published in the three bioenergy- or industrial-crop focused journals. The top three countries that published the highest levels of WoS Core Collection agricultural engineering articles in 2016 were China (1132), United States (669) and Brazil (474). The similar top publishing institutions were the United States Department of Agriculture (USDA; 136), Chinese Academy of Sciences (CAS; 136) and Indian Council for Scientific and Industrial Research (CSIR; 79). The results of the study also show that publishing by Chinese scientists in the 13 journals indexed in the JCR Agricultural Engineering (AE) category is rapidly increasing, with seven research institutions ranked in the global top 20 in 2016, based on studies published in journals indexed in the JCR agricultural engineering category. The analysis also reveals that the specialty journals (e.g., the three bioenergy-focused journals) are not directly comparable with the comprehensive agricultural engineering journals and should potentially be excluded from future versions of the JCR and WoS CC AE categories. Keywords: Web of Science, JCR, agricultural engineering, impact factor, USDA, CAS, comprehensive, specialty DOI: 10.25165/j.ijabe.20181105.3083 Citation: Wang Y J, Gassman P W, Wang Y K, Pu Y J. Analysis of journal content characteristics and metrics reported in the Clarivate Analytics Journal Citation Reports and Web of Science Core Collection Agricultural Engineering categories. Int J Agric & Biol Eng, 2018; 11(5): 1–26.